Pengembangan Lapangan TGB dengan Parameter Penambahan Sumur dan Keekonomian dengan Simulasi Reservoir. - Devita Putri Dwi Wijayanti (Fakultas Teknik, 2025)
The Tarakan Basin in North Kalimantan is one of Indonesia’s promising hydrocarbon provinces, comprising key geological formations such as the Meliat, Tabul, Santul, and Tarakan formations, which function respectively as source rock, reservoir, and seal. Prior to 2006, the region-particularly around Bunyu Island was considered a greenfield area due to limited geological data and the absence of major exploratory drilling. A turning point occurred with the drilling of exploration well A-01 in 2006, which successfully identified oil-bearing zones, particularly within the Tabul and Meliat Formations at moderate to deep depths. This study aims to evaluate development scenarios for the TGB Field through reservoir simulation combined with economic analysis, adopting a Production Sharing Contract (PSC) with a cost recovery scheme. The methodology includes literature review, experimental design, and reservoir simulation using CMG 2021 software, based on secondary data such as production history, petrophysical data, geological models, and pressure history. Simulation results show that incremental well development significantly improves reservoir drainage efficiency and hydrocarbon recovery. The base case scenario, with only one well (A-01), yields 562,188 STB with a recovery factor (RF) of 1.6%. Scenario 1 increases output to 2,995,186.8 STB (RF 8.65%), Scenario 2 to 4,288,737.6 STB (RF 12.38%), and Scenario 3 achieves the highest technical performance with 4,588,737.6 STB (RF 13.25%). While Scenario 3 delivers the best technical outcome, Scenario 2 emerges as the most economically feasible option, with a contractor NPV of USD 1.67 million, IRR of 12%, and a pay-out time of 7.82 years. Additionally, the government stands to gain USD 307 million in revenue and an NPV of USD 15.6 million. The combination of efficient cost recovery and balanced benefits makes Scenario 2 the most viable development strategy for the TGB Field.
Reuploud file repositori 12 mei 2026_Firli_Tata Approved by Teddy
Keywords: Tarakan Basin; Reservoir Simulation; Cost Recovery; Recovery Factor; Oil Field Economics.